Dependence of the distribution constant in liquid–liquid partition equilibria on the van der Waals molecular surface area. Issue 18 (12th August 2013) - Moldoveanu, Serban C.; David, Victor
<x xml:space="preserve">Abstract</x> The direct calculation of free energy of interactions between a solute j and two immiscible liquids shows a linear dependence between the (logarithm of) the distribution constant in liquid–liquid partition equilibrium log Kj and the van der Waals surface area of the solute. The study provides a thermodynamic proof for the formula log KBA, j = c1 log KBC, j + c2 that describes the linear dependence between (the logarithm of) the distribution constant for a solute j in a solvent system (B/A) and (the logarithm of) the distribution constant for the same solute in a different solvent system (B/C). This relation has been well proven by various experimental studies and it is frequently used in liquid chromatographic separations as well as in liquid–liquid extractions, but was not explained previously based on thermodynamic results. The theory was verified using the prediction of octanol/water distribution constants log Kow for a wide range of molecules, including hydrocarbons and compounds with a variety of functional groups. The results have also been verified for the distribution constants in other solvent systems. The expression for the distribution constant obtained in this study also gives a theoretical base for the additive fragment methodology used for the prediction of log Kow.